Dietary soybean meal utilization with phytase supplementation for hybrid F1, red sea bream (♀) × black sea bream (♂) - Kim, Yang Su; Amal Kumar Biswas; Ji, Seung Cheol; Yong, Annita Seok Kian; Biswajit K. Biswas; Osamu Takaoka; Osamu Murata; Kenji Takii (Japanese Society for Aquaculture Science, 2009)
The efficacy of replacing dietary fish meal with soybean meal for juvenile F1, red sea bream, Pagrus major female×black sea bream, Acanthopagrus schlegeli male, was assayed by growth and digestive performances. The F1 in triplicate tanks were fed each of following four diets: 46% fish meal (F), 30% fish meal＋20% soybean meal (S₂₀), 15% fish meal＋40% soybean meal (S₄₀) and S₄₀＋2500 phytase units (PU) /kg diet (S₄₀P) for 12 weeks. In F1, the diets S₂₀ and S₄₀P showed similar growth performance to that of F and S₄₀, but S₄₀ had significantly lower specific growth rate, feed conversion efficiency and energy efficiency as compared with F diet. The diet S₄₀ also led lower nutrient and phosphorus retentions than other diets, while the dietary treatments did not alter carcass and liver proximate compositions. Moreover, diet S₄₀P produced higher apparent nutrient and phosphorus digestibility than diet S₄₀, resulting in lower phosphorus discharge into surrounding water mass. These results reveal that a suitable replacement level of dietary fish meal with soybean meal is recommended about 67% with the co-supplementation of phytase at/under 2500 PU/kg diet under the experimental conditions used here.